Rethinking architectural historiography - Arnold, Dana; Ergut, Elvan Altan; Özkaya, Belgin Turan; ebrary, Inc. (London : Routledge, Taylor & Francis Group, 2006)
Rather than subscribing to a single position, this collection informs the reader about the current state of the discipline looking at changes across the broad field of methodological, theoretical and geographical plurality. Divided into three sections, Rethinking Architectural Historiography begins by renegotiating foundational and contemporary boundaries of architectural history in relation to other fields, such as art history and archaeology. It then goes on to critically engage with past and present histories, disclosing assumptions, biases and absences in architectural historiography. It concludes by exploring the possibilities provided by new perspectives, reframing the discipline in the light of new parameters and problematics. This timely and illustrated title reflects upon the current changes in historiographical practice, exploring potential openings that may contribute further transformation of the disciplines and theories on architectural historiography and addresses the current question of the disciplinary particularity of architectural history.
Part I, Boundaries -- 1, Art history and architectural history -- 2, Buildings archaeology: context and points of convergence -- 3, Architecture as evidence -- 4, Program and programs -- 5, Hercules at the roundabout: multidisciplinary choice in the history of architecture -- 6, Frontiers of fear: architectural history, the anchor and the sail -- Part II, Critical engagements -- 7, Questions of Ottoman identity and architectural history -- 8, In Ordinary Time: considerations on a video installation by Iñigo Manglano Ovalle and the New National Gallery in Berlin by Mies van der Rohe -- 9, Reopening the question of document in architectural historiography: reading (writing) Filarete's tratise on architecture for (in) Piero de' Medici's study -- 10, From architectural history to spatial writing -- 11, Presenting Ankara: popular conceptions of architecture and history -- Part III, Reframings -- 12, Space, time, and architectural history -- 13, Visuality and architectural history -- 14, The digital disciplinary divide: reactions to historical virtual reality models -- 15, The afterlife of buildings: architecture and Walter Benjamin's theory of history -- 16, Beyond a boundary: towards an architectural history of the non-east
Elektronická reprodukce.
Keywords: historiografie umění; dějiny architektury; art historiography; history of architecture; studie; sborníky; e-knihy online; studies; papers of several authors; e-books online